The Developmental Dynamics of Joining a Gang in Adolescence: Patterns and Predictors of Gang Membership - Gilman, Amanda B. (2014)
Researchers have examined the predictors of adolescent gang membership, finding significant factors in the neighborhood, family, school, peers, and individual domains. However, little is known about whether risk and protective factors differ in predictive salience at different developmental periods. The present study examines predictors of joining a gang, tests whether these factors have different effects at different ages, and whether they differ by gender using the Seattle Social Development Project (SSDP) sample (n=808). By age 19, 173 participants had joined a gang. Using survival analysis, results showed that unique predictors of gang membership onset included living with a gang member, antisocial neighborhood, and antisocial peer influences in the previous year. No time or gender interactions with predictors were statistically significant.